Pengalaman Keagamaan Santri Dalam Pembacaan Al-Ma’tsurat Di Pondok Pesantren Al-Kamal Kuwarasan Kebumen (Analisis Teori William James) - Taufiq Hidayat, Aditya; Munawir (Fakultas Ushuluddin Adab dan Humaniora (FUAH), Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2024)
This research aims to reveal the religious experiences of students through the Al-Ma'tsurat dhikr activity which is read regularly every day after the morning prayer and before sunset. Classified as field research using a structural phenomenology approach and then observing, interviewing and documenting as a data collection method. The subjects of this research were 6 male students in grades 5 and 6 of ulya at the Al-Kamal Islamic Boarding School. The theory used in this research is William James's theory of religious experience which includes the characteristics of ineffability, transience, noetic quality, passivity as well as emotional expressions in the categories of religious fear, religious joy and religious awe. The results obtained in this research were that after approximately 3 years of regularly reading Al-Ma'tsurat, participants experienced a feeling of being close to God, their parents' sustenance was made easier, they easily understood lessons and achieved what they dreamed of, and they felt protected and kept away from violating acts.